Biofabrication of magnetic nanoparticles and their use as carriers for pectinase and xylanase - Shady S. Hassan; Brendan Duffy; Gwilym A. Williams; Amit K. Jaiswal (Elsevier, 2022)
In this study, superparamagnetic iron oxide nanoparticles (MNPs) were synthesized via exposure of fungal cell filtrate from Aspergillus flavus to aqueous iron ions. The extracellular synthesis of MNPs was monitored by UV-Vis spectrophotometry and showed an absorption peak at 310 nm. The morphology of MNPs was found to be flake-like, as confirmed by Field Emission Scanning Electron Microscopy (FESEM), while the average crystallite size was ∼16 nm, as determined by X-ray diffraction (XRD). Energy dispersive X-ray (EDX) analysis was performed to confirm the presence of elemental Fe in the sample. Pectinase and xylanase were covalently immobilized on MNPs with efficiencies of ∼84% and 77%, respectively. Compared to the free enzymes, the immobilized enzymes were found to exhibit enhanced tolerance to variation of pH and temperature and demonstrated improved storage stability. Furthermore, the residual activity of the immobilized enzymes was about 56% for pectinase and 52% for xylanase, after four and three consecutive use cycles, respectively.